Genetic and Functional Characterization of ADAMTS13 Variants in a Patient Cohort with Upshaw–Schulman Syndrome Investigated in Germany - Hassenpflug, Wolf Achim; Obser, Tobias; Bode, Julia; Oyen, Florian; Budde, Ulrich; Schneppenheim, Sonja; Schneppenheim, Reinhard; Brehm, Maria Alexandra (Thrombosis and Haemostasis, 2018)
Upshaw–Schulman syndrome (USS) is caused by severe ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) deficiency due to homozygous or compound heterozygous mutations in the ADAMTS13 gene. Previous studies suggest three possible disease mechanisms: (1) reduced secretion of ADAMTS13 variants, (2) impaired proteolytic activity, (3) defective biosynthesis due to nonsense-mediated decay. Expression studies have failed to establish a clear genotype/phenotype correlation that could explain the significant variability in the age of onset and patients' clinical courses. In this study, we investigated ADAMTS13 sequence variations in 30 USS patients and identified 31 disease-causing mutations; among them 10 novel variants. While none of the recombinant proteins exhibited significant retention in the endoplasmic reticulum, secretion and activity analysis revealed defective release for all but one missense mutant. The latter exhibited normal secretion but impaired activity due to inactivation of the catalytic domain. Truncated mutants showed secretion and residual activity even though the patients suffered from a severe phenotype. The expression systems which we used may not be appropriate here, as they do not assess nonsense-mediated decay causing degradation of mRNA. In some patients, phenotypic severity could be explained by the combined effects of two mutations. Genetic screening in combination with in vitro characterization of ADAMTS13 variants from both alleles is a valuable tool to predict the phenotypic severity of USS. When necessary, supplementary methods, such as kinetics under flow conditions and mRNA processing assays, can be included. Such data are helpful to identify patients who are at high risk for severe attacks and therefore might benefit from prophylactic treatment.
Keywords: ADAMS/ADAMTS13; von Willebrand factor; thrombotic thrombocytopenic purpura; thrombocytopenia